Profitability, performance and the impacts of Lean philosophy on business efficiency - Santos, Matheus Alves dos; Gomes, Vanielle Aparecida do Patrocinio; Gonçalves, Wellington; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2025)
This study presents a bibliometric analysis focused on the impact of Lean Manufacturing on companies’ profitability and performance, based on publications indexed in the Scopus and Web of Science databases. Statistical tools were applied to map the evolution of research and identify key themes addressed in the literature. The results highlight a significant growth in publications on the topic and emphasize factors such as leadership, organizational culture, and strategic alignment as crucial elements for the success of the Lean methodology. The research provides valuable insights into Lean’s influence on business efficiency, underscoring the need for tailored approaches for its effective implementation.